2016
DOI: 10.1038/srep37989
|View full text |Cite
|
Sign up to set email alerts
|

A possible space-based tsunami early warning system using observations of the tsunami ionospheric hole

Abstract: Ionospheric plasma disturbances after a large tsunami can be detected by measurement of the total electron content (TEC) between a Global Positioning System (GPS) satellite and its ground-based receivers. TEC depression lasting for a few minutes to tens of minutes termed as tsunami ionospheric hole (TIH) is formed above the tsunami source area. Here we describe the quantitative relationship between initial tsunami height and the TEC depression rate caused by a TIH from seven tsunamigenic earthquakes in Japan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 35 publications
(55 reference statements)
1
50
0
Order By: Relevance
“…Astafyeva and Shults (2019) also noted that lower resolution data sampling, such as 15 or 30 s, which so far is a standard resolution for GNSS data, will, most likely, not work efficiently. Kamogawa et al (2016) suggested a method based on observations of "tsunami-ionospheric hole" as potentially useful for near real-time tsunami warnings. Kamogawa et al (2016) found a quantitative relationship between the initial tsunami height and the TEC depression rate caused by the hole from seven tsunamigenic earthquakes in Japan and Chile.…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%
“…Astafyeva and Shults (2019) also noted that lower resolution data sampling, such as 15 or 30 s, which so far is a standard resolution for GNSS data, will, most likely, not work efficiently. Kamogawa et al (2016) suggested a method based on observations of "tsunami-ionospheric hole" as potentially useful for near real-time tsunami warnings. Kamogawa et al (2016) found a quantitative relationship between the initial tsunami height and the TEC depression rate caused by the hole from seven tsunamigenic earthquakes in Japan and Chile.…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%
“…The use of ionospheric signals measured by Global Navigation Satellite Systems (GNSS) (Artru et al, ; Kamogawa et al, ; Occhipinti et al, ; Rolland et al, ) has therefore been proposed in many papers as a means of completing and improving tsunami warning systems, from the early proposals of Hines () and Peltier and Hines () to a first patent proposing to extract the total electron content (TEC) from dual‐frequency satellite systems (MacDoran, ) and finally to the most recent research papers (Kamogawa et al, ; Savastano et al, ). However, none of these works have demonstrated that TEC signals could be used to reproduce the signals recorded by the DART buoys with an accuracy compliant with that required for warning systems.…”
Section: Introductionmentioning
confidence: 99%
“…Najita et al () first proposed to use a network of Doppler sounders to capture Rayleigh‐surface‐wave induced ionospheric perturbations, which propagates much faster than tsunamis. Kamogawa et al () explored the possibility of use existing ground GPS receiver network to detect TEC perturbations in the epicentral zone and correlate the TEC perturbations with the initial tsunami height for several tsunamigenic earthquakes. The first concept depends on the knowledge of the earthquake‐tsunami dynamic coupling and of the tsunami generation mechanisms, which are not well understood as of today.…”
Section: Most Recent Advances and Future Directionsmentioning
confidence: 99%